2007
DOI: 10.1590/s0036-46652007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Performances of HTLV serological tests in diagnosing HTLV infection in high-risk population of São Paulo, Brazil

Abstract: SUMMARYTesting problems in diagnosing human T-lymphotropic virus (HTLV) infection, mostly HTLV-II, have been documented in HIV/AIDS patients. Since December 1998, the Immunology Department of Instituto Adolfo Lutz (IAL) offers HTLV-I/II serology to Public Health Units that attend HTLV high-risk individuals. Two thousand, three hundred and twelve serum samples: 1,393 from AIDS Reference Centers (Group I), and 919 from HTLV out-patient clinics (Group II) were sent to IAL for HTLV-I/II antibodies detection. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Such HTLV indeterminate WB patterns have been reported, for the last 20 years, by several authors and are found mainly, and their signification studied, in tropical areas, such as Central Africa and Southeast Asia (24,28,31,41,47,54). However, they have also been reported in other areas, such as European countries (68), the United States (11,51,73), the Caribbean area (17,57), Central and South America (Brazil, Argentina) (6,35,44,50,61), and more recently the Middle East (74). Most of the studies concern blood donors (10,11,16,63) or epidemiological work in the general population (43) but also organ donors for transplantation (22,36), lactariums (19,58,70), and neurological patients (1,73).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Such HTLV indeterminate WB patterns have been reported, for the last 20 years, by several authors and are found mainly, and their signification studied, in tropical areas, such as Central Africa and Southeast Asia (24,28,31,41,47,54). However, they have also been reported in other areas, such as European countries (68), the United States (11,51,73), the Caribbean area (17,57), Central and South America (Brazil, Argentina) (6,35,44,50,61), and more recently the Middle East (74). Most of the studies concern blood donors (10,11,16,63) or epidemiological work in the general population (43) but also organ donors for transplantation (22,36), lactariums (19,58,70), and neurological patients (1,73).…”
Section: Discussionmentioning
confidence: 74%
“…Screening tests are usually enzyme-linked immunoassorbent assays (ELISAs) (3,5,18,43,66) or particle agglutination (PA) (33). Confirmatory tests are immunofluorescence (IF) (23) but mostly Western blot (WB) analyses (30,35,38,39,64,71). Moreover, research of integrated provirus, in the DNA from peripheral blood cells, could be done by qualitative and/or quantitative PCR (2,4,8,68).…”
mentioning
confidence: 99%
“…Brazil 5,6,14,15 , and suggested the use of two ELISAs of different compounds and formats for screening in this country (contrary to the recommendation of the Ministry of Health of Brazil) 16 . The same strategy has been conducted in Argentina, where the combination of two HTLV screening assays was shown to be useful for blood banks 3 .…”
Section: Resultsmentioning
confidence: 97%
“…The result is more frequent in low-risk blood donors, causing the loss of haemocomponents in blood centres and affecting the counseling of the donors [Lal et al, 1992a;Mauclère et al, 1997;Césaire et al, 1999;Lu and Chen, 2003;Berini et al, 2007;Jacob et al, 2007]. Certain indeterminate WB patterns, like HTLV-1 Gag indeterminate profile (HGIP), have been interpreted as seronegative [Césaire et al, 1999], but the possibility of true HTLV-1 infection should be take into consideration, especially in blood donors living in endemic areas, in intravenous drug users and in patients with neurological diseases.…”
Section: Introductionmentioning
confidence: 99%